Mạng xã hội Facebook với việc tiếp cận và quảng bá các hoạt động dịch vụ thư viện - Trần, Xuân Bản (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
This paper discusses the effectiveness of the academic libraries in approaching and promoting library services to students through Facebook. It investigates the method of organising Facbook pages, content and frequency of posting on the pages from 30 academic libraries in Viet Nam. It proposes solutions to improve the Facebook effectiveness.